2019
DOI: 10.18203/2320-1770.ijrcog20190981
|View full text |Cite
|
Sign up to set email alerts
|

Admission test cardiotocography in labour as a predictor of foetal outcome in high risk pregnancies

Abstract: Background: Continuous fetal heart monitoring in all pregnant women in labour has gained prominence in obstetric practice in the recent years. The aim of this study was to emphasize on the role of admission cardiotocography (CTG) in labour as a predictor of foetal outcome in high risk pregnancies. Methods: This was a prospective observational study done on 340 high risk patients admitted in labour with a period of gestation of ≥37 weeks. An admission CTG which consists of a 20-minute recording of FHR and uteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 8 publications
3
6
0
Order By: Relevance
“…Bix et al analyzed three trials and found that the admission CTG was not effective in predicting neonatal outcomes [18]. [19][20][21][22]. Our study also backed the findings of these studies.…”
Section: Discussionsupporting
confidence: 84%
“…Bix et al analyzed three trials and found that the admission CTG was not effective in predicting neonatal outcomes [18]. [19][20][21][22]. Our study also backed the findings of these studies.…”
Section: Discussionsupporting
confidence: 84%
“…Neonatal admission was higher in the pathological group, since only 7 (4%) fetuses with reactive CTG and 24 (18.4%) fetuses from the suspicious group compared to 53 (49.5%) fetuses from the pathological CTG group were admitted in NICU, thus, the difference was statistically significant with p-value <.05. A similar result was seen in the study conducted by Kumar et al [13], where 44.5% of babies with non-reactive CTG and 6% of babies with reactive CTG were admitted to the nursery. Atul K Sood et al [11] in their study found that there was a significant correlation between APGAR <7 and neonatal admission and was more commonly associated with non-reactive tracing, as 11.2% of babies with non-reactive CTG were admitted in NICU.…”
Section: Discussionsupporting
confidence: 87%
“…Similar results were reported in several other studies. 6,11,15,17 A higher incidence of LSCS for foetal distress was observed in high risk patients (25%) compared to low risk patients (2%) in the present study. This is probably the result of misclassification of more foetuses as suspicious or pathological AT (high false positives).…”
Section: Atmentioning
confidence: 42%
“…In the present study, the proportion of patients with a reactive AT, suspicious AT, and pathological AT were comparable to results in similar studies. 5,6,[11][12][13] The shortcomings of a single AT in predicting foetal distress in the setting of protracted labour and problems of cord have been described in several studies. 5,[12][13][14][15] Foetal distress was present in 11 (7.05%) patients with a normal AT in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation